Cleaning production method of R-3,5-bis(trifluoromethyl) phenyl ethanol - ZHU HUILIN (2017)
The invention discloses a cleaning production method of R-3,5-bis(trifluoromethyl) phenyl ethanol. Alcohol dehydrogenase is immobilized, and immobilized enzymes are obtained, then, the immobilized enzymes are used as biocatalysts to catalyze a 3,5-bis(trifluoromethyl) acetophenone substrate, and thus the R-3,5-bis(trifluoromethyl) phenyl ethanol is generated. The cleaning production method of the R-3,5-bis(trifluoromethyl) phenyl ethanol has the advantages that the reaction condition is simple, the conversion rate is high, the reaction period is short, reaction selectivity is high, the cost is low, and reaction raw materials can be recycled and is an environment-friendly energy-saving efficient production process. 本发明公开了种R-3,5-双三氟甲基苯乙醇的清洁生产方法，将醇脱氢酶固定化得固定化酶，然后将所得固定化酶作为生物催化剂催化底物3,5-双三氟甲基苯乙酮生成R-3,5-(双三氟甲基)苯乙醇。本发明具有反应条件简单，转化率高，反应周期短，反应选择性高，成本低，反应原材料可重复利用等优点，是种绿色节能的高效生产工艺。